2017
DOI: 10.1371/journal.pone.0184343
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle traversal and route choice in flying honeybees: Evidence for individual handedness

Abstract: Flying insects constantly face the challenge of choosing efficient, safe and collision-free routes while navigating through dense foliage. We examined the route-choice behavior of foraging honeybees when they encountered a barrier which could be traversed by flying through one of two apertures, positioned side by side. When the bees’ choice behavior was averaged over the entire tested population, the two apertures were chosen with equal frequency when they were equally wide. When the apertures were of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…2A, last row). While it is tempting to discuss this in the context of laterality, for which there is evidence in ants and bees at both the population and individual level (Basari et al, 2014;Frasnelli et al, 2012;Hunt et al, 2014;Ong et al, 2017), we think that is not the case here. We think the bias may be Table S1).…”
Section: Discussionmentioning
confidence: 84%
“…2A, last row). While it is tempting to discuss this in the context of laterality, for which there is evidence in ants and bees at both the population and individual level (Basari et al, 2014;Frasnelli et al, 2012;Hunt et al, 2014;Ong et al, 2017), we think that is not the case here. We think the bias may be Table S1).…”
Section: Discussionmentioning
confidence: 84%
“…Obstacle and gap detection may thus be considered the most basic element of flight through clutter. A few recent studies have analysed the response of flying insects in minimally cluttered environments and revealed that when confronted with obstacles with varying spacing, insects such as bumblebees and honeybees choose the larger gap (Baird and Dacke, 2016; Ong et al, 2017). This might seem as an obvious response, yet it highlights the active response of insects in avoiding collisions, which otherwise can result in irreparable damage to body and wings.…”
Section: Introductionmentioning
confidence: 99%
“…Further support for the existence of individual handedness has since been reported for many invertebrates , including ants Endlein & Sitti, 2018), bees (Ong et al, 2017), and giant water bugs Belostoma flumineum Say (Heteroptera: Belostomatidae) (Kight et al, 2008). reported an interesting context-dependent handedness in desert locusts (Schistocerca gregaria).…”
Section: Introductionmentioning
confidence: 89%